Growth Response and Yield of Sweet Corn on Palm Oil Sludge and Dolomite in Ultisols - Herry Gusmara; Ricci Handoko Silitonga; Bilman Wilman Simanihuruk (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2020)
Sweet corn is a very popular agricultural commodity in Indonesia, so the production of sweet corn needs to be increased. One of the problems that often encountered in the field is the lack of availability of fertile land that can support the growth of sweet corn. Therefore it needs technology to increase land productivity. In this case, the use of palm oil sludge as a source of organic matter and dolomite as a material that can improve soil fertility. The purpose of this research is to get the dosage of palm oil sludge and dolomite that optimal for the growth and yield of sweet corn. This research was conducted from December 2017 to March 2018 in Air Sebakul Village, Talang Empat Subdistrict, Central Bengkulu using Randomized Completely Block Design with two treatment factors. The first factor is the dosage of palm oil sludge consisting of three levels, namely 0 tons ha-1, 10 tons ha-1, and 20 tons ha-1. The second factor is dolomite dosage consisting of four levels, namely 0 tons ha-1, 2 tons ha-1, 4 ton ha-1, and 6 ton ha-1so that 36 sample units are obtained. The results showed that the best combination was obtained from 10 ton ha-1 palm oil sludge and 3,61 tons ha-1 dolomite, which was able to produce the diameter of corn crop stalks of 1,98 cm. The single palm oil sludge treatment gave no significant effect on all growth and yield variables. The addition of dolomite dosage up to 6 tons ha-1 was able to increase plant height, total leaf area, the weight of corn without cornhusk, length of corn without cornhusk, a diameter of corn without cornhusk, fresh weight of the plant, and dry weight of the plant.